Prospects of Security Agencies’ Cooperation in Nepal - Upreti, Yukesh (Unity Journal, 2025)
In this ever-changing and dynamic global security environment, the need for security agency cooperation has been an integral part of national security. Security agency cooperation refers to the collaborative efforts among various national and international agencies aimed at achieving mutual security objectives through resource sharing, coordinated actions, and information exchange. In the context of Nepal, different internal and external factors have necessitated security agency cooperation to concentrate on profound national security. Currently, four security agencies are mandated in an umbrella framework of national security to promote national sovereignty, territorial integrity, and national unity. Notably, research conducted on national security has suggested enhancing security agency cooperation to counter the persistent threats to the nation. This paper aims to assess the effectiveness of security agencies cooperation in Nepal along with its benefit and challenges. The methodology engaged to meet the objective of research is a qualitative approach with descriptive and analytical research design. The research tool used by the researcher is an in-depth interview with ten key informants for accurate and authentic data. The acquired data are codified, and themes are analyzed through non-numeric unstructured data indexing, searching, and theorizing (NVIVO) software. The findings show that security agency cooperation is progressive in nature, and it would benefit from prompt service delivery, crisis responses, the formation of strong intelligence mechanisms, national and international recognition, and improved border security. Challenges such as legal jurisdiction, citizen distrust, lack of technical knowledge, and leadership apathy exist as major hindrances. The research suggests revising the role of the National Security Council, constructing an integrated command post, establishing a joint intelligence mechanism, and implementing a leadership familiarization program to enhance security agency cooperation